2014
DOI: 10.1007/s12038-014-9460-x
|View full text |Cite
|
Sign up to set email alerts
|

Skin anti-photoaging properties of ginsenoside Rh2 epimers in UV-B-irradiated human keratinocyte cells

Abstract: Ginseng, one of the most widely used herbal medicines, has a wide range of therapeutic and pharmacological applications. Ginsenosides are the major bioactive ingredients of ginseng, which are responsible for various pharmacological activities of ginseng. Ginsenoside Rh2, known as an antitumour ginsenoside, exists as two different stereoisomeric forms, 20(S)-ginsenoside Rh2 [20(S)-Rh2] and 20(R)-ginsenoside Rh2 [20(R)-Rh2]. This work aimed to assess and compare skin anti-photoaging activities of 20(S)-Rh2 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The ginseng saponin, ginsenoside Rh1, was shown that to reduce IgE and IL-6 levels and inflammatory symptoms induced by oxazolone in hairless mice (Zheng et al 2011). In addition, ginsenosides Rh2 and Rg3 were demonstrated for decrease of ear thickness and anti-inflammatory effects in mast cells and animal models (Oh et al 2014). Furthermore, P. ginseng leaf extract contains several phytochemicals such as ginsenosides, flavonoids, polysaccharides, and triterpenoids, which are responsible for the various pharmacological activities (Jung et al 2005, Wang et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…The ginseng saponin, ginsenoside Rh1, was shown that to reduce IgE and IL-6 levels and inflammatory symptoms induced by oxazolone in hairless mice (Zheng et al 2011). In addition, ginsenosides Rh2 and Rg3 were demonstrated for decrease of ear thickness and anti-inflammatory effects in mast cells and animal models (Oh et al 2014). Furthermore, P. ginseng leaf extract contains several phytochemicals such as ginsenosides, flavonoids, polysaccharides, and triterpenoids, which are responsible for the various pharmacological activities (Jung et al 2005, Wang et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosides are one of the primary bioactive ingredients in ginseng, which have various pharmacological effects including anti-obesity, anti-diabetic, regulation of blood pressure, anti-aging, immune regulation and anti-tumor functions (18)(19)(20)(21)(22). Ginsenosides are classified into three types, including protopanaxatriol-type, oleanolic acid-type and protopanaxadiol-type ginsenosides (23). Ginsenoside 20(S)-Rh2 (GRh2) belongs to the protopanaxadiol-type ginsenoside group.…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides are the main active chemical constituents of ginseng, the root of Panax ginseng Meyer [18] , which has great pharmacological efficacy to promote the human health in global traditional medicine, such as antidiabetic, anti-inflammatory, antitumor, anti-UV radial, protection of nerves, regulation of blood pressure, and other functions [19] , [20] , [21] , [22] . Ginsenosides could be classified in three types based on aglycone moieties: protopanaxadiol-type ginsenosides, protopanaxatriol-type ginsenosides, and oleanolic acid-type ginsenosides [22] . Ginsenoside Rh2 (GRh2), identified as an protopanaxadiol-type ginsenoside, exhibits significant antitumor effects on pancreatic cancer, leukemia, prostatic cancer, skin squamous cell carcinoma, glioblastoma, and so on [23] , [24] , [25] , [26] , [27] .…”
Section: Introductionmentioning
confidence: 99%